(untitled) (Academia Science Repository, 2023)
In this article , temperament is the character of a person The information obtained from R. Cloninger’s questionnaire is presented. Also, the problem of completeness of therapeutic treatment in somatic diseases and related theories and concepts are interpreted, the fact that the main problem has not been directly studied, the relevance of this issue, the psychological characteristics of the patient, the clinical characteristics of the disease, the characteristics of the treatment program, the influence of social factors and the factors of the organization of medical care. done